Gay Masculinity or Homonormalization?Characters in Un Rubio and Taekwondo - Silva Montero, Alonso Rafael (2025)
In this article, we aim to initiate a discussion linked to the category of homonormativity in relation to the portrayal of the main characters in Marco Berger’s films Un Rubio and Taekwondo. This debate arises from an analysis of the characters’ construction in physical, psychological, and social terms. Likewise, a theoretical overview of homonormalization and Argentine gay cinema is provided. Although it is understood that Berger depicts a form of gay masculinity –or men who challenge certain affective and sexual heteronormative practices in Latin America–, the text leaves space to explore whether this may lead to the must of setting gay characters within the heteronormative system.